Hadronic energy resolution of a highly granular scintillator-steel hadron calorimeter using software compensation techniques - Adloff, Catherine; Eckert, Patrick; Harion, Tobias; Kaplan, Alexander; Schultz-Coulon, Hans-Christian; Shen, Wei; Stamen, Rainer; Tadday, Klaus Alexander (Journal of Instrumentation, 2012)
The energy resolution of a highly granular 1 m 3 analogue scintillator-steel hadronic calorimeter is studied using charged pions with energies from 10 GeV to 80 GeV at the CERN SPS. The energy resolution for single hadrons is determined to be approximately 58%/√ E /GeV. This resolution is improved to approximately 45%/√ E /GeV with software compensation techniques. These techniques take advantage of the event-by-event information about the substructure of hadronic showers which is provided by the imaging capabilities of the calorimeter. The energy reconstruction is improved either with corrections based on the local energy density or by applying a single correction factor to the event energy sum derived from a global measure of the shower energy density. The application of the compensation algorithms to geant 4 simulations yield resolution improvements comparable to those observed for real data.